The Impact of Poverty, Level of Education and Missed Diagnosis on the Outcome of Management of Obstructing Stone: A Paradigm of Poor Urology Service - Taha, Sami Mahjoub; Ahmed, Mohammed Al Imam Mohammed; Ibrahim, Nadir; Elhassan, Moawia Mohammed Ali (مجلة الجزيرة للعلوم الصحية; مجلد 13 عدد 1 (2017), 2017)
Objective: To study the causes and outcome of delayed presentation in patients with obstructive uropathy due to stones in a tertiary referral hospital in Central Sudan. Methodology: This is a prospective cross-sectional hospital based study carried out in the urology department of the Gezira Hospital for Urology and Renal diseases. Results :The total number of the study group was 140 patients. The mean age at presentation was 42.17±16.975 year with a male-to-female ratio of 1.7:1. The period from the time of onset of symptoms to the time of diagnosis was less than two weeks in 21.2% of  cases and more than two weeks in 78.5% of cases. The reasons of delayed presentation (> two weeks) included missed management by healthcare professionals in 85 (60.7 %), patients ignorance in 16 (11.5%), and financial issues in 9 (6.4%) patients. At presentation, 25.7% of patients presented with abnormal renal function. Post intervention, complete recovery was achieved in 50% of patients with impaired renal function. The degree of renal recovery was dependent primarily on duration of symptoms. Conclusion: This study has shown that there was delayed presentation of patients with obstructive uropathy due renal stones in our setting. Missed management by healthcare professionals was the most common cause of delayed presentation. The duration of symptoms was directly related to post intervention serum creatinine levels. Efforts at improving awareness and early diagnosis among the health team should be made to improve treatment outcome.